Implementation of the Electronic System for Collection of Value-Added Tax on Trade: Appointing Foreign and Local Companies as Collectors - Wildan Arif; Ning Rahayu (Universitas Teuku Umar, 2023)
The large number of offers of services and goods in utilizing digitalization is the background for the PMSE VAT policy in increasing state income broadly and evenly. PSME's VAT policy is also faced with the challenge of creating equality in terms of paying state contributions between traditional businessmen and economic activities that use the internet or among domestic businesses. Selection Appointment of entrepreneurs to collect electronic trade with PKP who have not been appointed as collectors creates inequality in terms of paying taxes and reporting SPT where every company appointed as PMSE collector is required to report reporting in accordance with rules and policies. This study aims to determine the PMSE VAT collection policy through the appointment of local digital companies that have and have not been appointed as PMSE VAT collectors in paying attention to the principles of a good taxation system and knowing the level playing field of local companies that have and have not been appoint PMSE VAT collector based on the theory of fairness. The type of assessment in this thesis uses qualitative methods with literature studies and interviews. Informants in this study were staff of the fiscal policy agency, staff of the directorate general of taxation, lecturers and tax consultants. The conclusions obtained explain that the policy in collecting electronic sales tax to pay attention to the principles of a good taxation system has not been properly fulfilled.